1999
DOI: 10.1021/np980501m
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antiinflammatory Activities of Anthocyanins and Their Aglycon, Cyanidin, from Tart Cherries

Abstract: The anthocyanins (1-3) and cyanidin isolated from tart cherries exhibited in vitro antioxidant and antiinflammatory activities comparable to commercial products. The inhibition of lipid peroxidation of anthocyanins 1-3 and their aglycon, cyanidin, were 39, 70, 75, and 57%, respectively, at 2-mM concentrations. The antioxidant activities of 1-3 and cyanidin were comparable to the antioxidant activities of tert-butylhydroquinone and butylated hydroxytoluene and superior to vitamin E at 2-mM concentrations. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
300
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(309 citation statements)
references
References 10 publications
4
300
0
5
Order By: Relevance
“…Cyclo-oxygenase inhibitory flavonoids (Seeram et al, 2001;Wang et al, 1999) and anthocynanins with high antioxidant and anti-inflammatory activities (Blando et al, 2004;Tall et al, 2004) have been identified in tart cherries, which are considered good sources of phenolic compounds. This has led to speculation that tart cherry consumption may be effective in alleviating symptoms in inflammatory conditions (Tall et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclo-oxygenase inhibitory flavonoids (Seeram et al, 2001;Wang et al, 1999) and anthocynanins with high antioxidant and anti-inflammatory activities (Blando et al, 2004;Tall et al, 2004) have been identified in tart cherries, which are considered good sources of phenolic compounds. This has led to speculation that tart cherry consumption may be effective in alleviating symptoms in inflammatory conditions (Tall et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous antioxidant and anti-inflammatory agents have been identified in plants purported to reduce illness and disease associated with inflammation and tissue damage. Specifically, the disease modifying agents include cyclo-oxygenase inhibitory flavonoides (Seeram, Bourquin, & Nair, 2001;Wang et al, 1999) and anthocynanins with high antioxidant and anti-inflammatory activities (Blando, Gerardi, & Nicoletti, 2004;Tall et al, 2004). These have been identified in natural foods from black tea to tart cherries to fish oil.…”
Section: Introductionmentioning
confidence: 99%
“…Despite previous studies in cell culture and animal 40 models, where cherry extracts have been shown to exert a range of cardio-protective effects [12,5], there has…”
mentioning
confidence: 95%
“…5 mg protein/mL in 0.1 M Tris/HCl, pH 7.8), a homogeneous protein purified from ram seminal according to the previously published procedures. 26 The rate of oxygen consumption during the initial phase of the enzyme-mediated reaction, with arachidonic acid as substrate was measured using a Model 5300 biological oxygen monitor (Yellow Spring Instruments, Inc., Yellow Springs, OH). Each assay mixture consisted of 0.1 M Tris/HCl, pH 7.8, 1.0 mM phenol, 17 µg hemoglobin, and 10 µM arachidonic acid.…”
Section: Methodsmentioning
confidence: 99%